Vegetation restoration patterns shape microbial functional coupling of soil carbon and nitrogen in arid coal-mining areas - Chuning Ji; Ziheng Song; Suo Zhang; Junliang Dong; Chuangang Gong; Jian Zhang; Guiyuan Wang; Xiaobin Li; Rulin Xiao; Ling Wu; Jihong Dong; Yanli Huang (Applied Soil Ecology, 2026)

The role of exposure on the vertical variation of mudflat sediment erodibility - Chuning Dong; Yongping Chen; Ian Townend; Yiming Wu; Zichao Guo; Qin Jiang; Giovanni Coco; Karin R. Bryan; Zeng Zhou (Marine Geology, 2025)

Wave attenuation by flattened vegetation (Scirpus mariqueter) - Yuxi Ma; Longhuan Zhu; Zhong Peng; Liming Xue; Wenzhen Zhao; Tianyou Li; Shiwei Lin; Tjeerd J. Bouma; Bas Hofland; Chuning Dong; Xiuzhen Li (Frontiers in Marine Science, 2023)
With the capacity to reduce wave energy and trap sediment, Scirpus mariqueter has become an important native species of annual grass for ecology restoration at the Yangtze Estuary in eastern China. Due to seasonal variances of biophysical characteristics, S. mariqueter usually bends and breaks in winter, resulting in flattened stems that may reduce its wave attenuation capacity. To investigate the effects of vegetation flattening on wave attenuation, a set of flume experiments were conducted for flattened and standing vegetation under different wave conditions. The model vegetation was designed to represent the wilted S. mariqueter collected in winter with dynamic similarity. Results showed that the wave damping coefficient for flattened vegetation ( β F ) was 33.6%-72.4% of that for standing vegetation ( β S ) with the same vegetation length. Both β F and β S increased with wave height but decreased with water depth. A wave attenuation indicator ( WAI ) was defined to generate empirical formulas for β S and β F as well as their ratio β F /β S . The empirical formulas were then applied to modify the existing standing vegetation-based wave attenuation model for flattened vegetation and performed successfully. Understanding the wave attenuation characteristics of flattened vegetation is essential for the management of ecological restoration and coastal protection.